The Effect of Principal's Leadership and Professional Competency on The Performance of School Counselors - Yoga Saputra, Surya; Puji Sugiharto, Dwi Yuwono; Awalya, Awalya (Jurnal Bimbingan Konseling, 2021)
The performance of school counselors is important for further research because it is related to the quality of counseling services in schools. The purpose of this study was to analyze the influence of Principal Leadership and Professional Competence on the Performance of Guidance and Counseling Teachers at SMPNs throughout Grobogan Regency. A total of 50 counselors were involved as respondents in the survey. The results of these findings indicate that the professional competence of teachers and principals' leadership have a simultaneous effect on teacher performance. The analysis technique uses regression analysis, hypothesis testing using the F test and t test. After analyzing, that the contribution of the principal's leadership and professional competence to the performance of school counselors at public junior high schools in Grobogan Regency is 67.6%.